2020
DOI: 10.1136/bmjpo-2019-000619
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide, population-based study of school grades in practical and aesthetic subjects of children treated for brain tumour

Abstract: BackgroundChildren treated for brain tumour (hereafter termed paediatric brain tumour survivors (PBTS)) often need extra support in school because of late-appearing side effects after their treatment. We explored how this group of children perform in the five practical and aesthetic (PRAEST) subjects: home and consumer studies, physical education and health, art, crafts and music.MethodsIn this nationwide population-based study of data from the Swedish Childhood Cancer Registry and Statistics Sweden, we includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 22 publications
2
11
1
Order By: Relevance
“…As in our two previous studies on academic grades in theoretical [ 13 ] and practical aesthetical subjects [ 14 ], there were no significant differences between the PBTS treated for high- or low-grade tumours in their national test performance, with the exception of missing information from the subtest reading/listening in Swedish, which became significant when fathers’ educations were taken into account. While our previous studies evinced significant differences within the PBTS group between girls and boys and their final grades in most theoretical and practical aesthetic subjects [ 13 , 14 ], this difference was not seen for the national tests. Still, when comparing the PBTS to controls, differences between the girls and boys were detected, as the odds for missing information from the national tests or to fail the national tests were higher for female PBTS compared with their controls than for male PBTS compared with their controls.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…As in our two previous studies on academic grades in theoretical [ 13 ] and practical aesthetical subjects [ 14 ], there were no significant differences between the PBTS treated for high- or low-grade tumours in their national test performance, with the exception of missing information from the subtest reading/listening in Swedish, which became significant when fathers’ educations were taken into account. While our previous studies evinced significant differences within the PBTS group between girls and boys and their final grades in most theoretical and practical aesthetic subjects [ 13 , 14 ], this difference was not seen for the national tests. Still, when comparing the PBTS to controls, differences between the girls and boys were detected, as the odds for missing information from the national tests or to fail the national tests were higher for female PBTS compared with their controls than for male PBTS compared with their controls.…”
Section: Discussionsupporting
confidence: 68%
“…The results showed that PBTS performed significantly worse compared with controls in all subjects and evinced a higher frequency of missing information and fail, but there were considerable differences between the subtests. Previous studies [ 10 , 11 , 12 , 13 , 14 ] showed that PBTS in general have lower grades compared with controls, so this was anticipated. Compared with our study of final grades in these subjects [ 13 ], the odds ratios for PBTS to fail the national tests compared with the controls were smaller than for having fail as their final grade.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations